2016
DOI: 10.5588/ijtld.15.0457
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of latent tuberculous infection among persons with pre-diabetes and diabetes mellitus

Abstract: SUMMARY SETTING Although diabetes mellitus (DM) is an established risk factor for active tuberculosis (TB) disease, little is known about the association between pre-DM, DM, and latent tuberculous infection (LTBI). OBJECTIVE To estimate the association between DM and LTBI. DESIGN We conducted a cross-sectional study among recently arrived refugees seen at a health clinic in Atlanta, GA, USA, between 2013 and 2014. Patients were screened for DM using glycosylated-hemoglobin (HbA1c), and for LTBI using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
4
45
1
1
Order By: Relevance
“…The prevalence of 8.2% for PDM in this study is similar to the reported 6.2% in Oke-Ogun region of Oyo state, Nigeria [32] and the 8.5% in Tamil-Nadu, India [33] but significantly different from the 13.8% recorded for periurban Uganda [34] and the 33.8% observed among recentlyarrived refugees in Atlanta, USA [35]. The high prevalence of 23.6% for LTBI in this work is also similar to the reported rates in other African countries, which ranged from 31.2% in Ethiopia [36] to 49.0% in urban Uganda [37] and 55.2% in South Africa [38]; while the American study reported 31.3% [35]. It is noteworthy that it was only the American study that simultaneously screened for both PDM and LTBI and used standardized techniques as employed in the present work.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of 8.2% for PDM in this study is similar to the reported 6.2% in Oke-Ogun region of Oyo state, Nigeria [32] and the 8.5% in Tamil-Nadu, India [33] but significantly different from the 13.8% recorded for periurban Uganda [34] and the 33.8% observed among recentlyarrived refugees in Atlanta, USA [35]. The high prevalence of 23.6% for LTBI in this work is also similar to the reported rates in other African countries, which ranged from 31.2% in Ethiopia [36] to 49.0% in urban Uganda [37] and 55.2% in South Africa [38]; while the American study reported 31.3% [35]. It is noteworthy that it was only the American study that simultaneously screened for both PDM and LTBI and used standardized techniques as employed in the present work.…”
Section: Discussionsupporting
confidence: 82%
“…The association between type-2 diabetes mellitus (DM) and pulmonary tuberculosis (TB) is well-documented (1,2,3,4,5,35), and it is recognized that most individuals do not just develop DM and TB overnight, they go through prolonged intermediate phase of pre-diabetes (PDM) and latent tuberculosis infection (LTBI) respectively. However, there is paucity of data on PDM and LTBI from the DM-and TB laden countries to inform recommendations on intervention in those settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference was not significant after controlling for confounders (81). Among refugees in Atlanta, US, there was a higher proportion of LTBI among those with pre-DM or DM (versus non-DM) when using QFT-IT (84) Thus, the few available studies do not indicate a clear compromise due to DM, but studies are needed to understand the individual contribution of DM and its synergy with additional host factors (older age, gender, BMI) that can collectively influence assay sensitivity.…”
Section: Biological Basis For the Association Between Tb And Dmmentioning
confidence: 99%
“…PDM has been shown recently to be associated with an increased risk of latent TB infection [7], to be associated with pulmonary TB in individuals with respiratory symptoms [8], and to be associated with dysregulated cytokine responses in pulmonary TB [9]. In addition, the prevalence of PDM has been reported to be as high as 25% in individuals with active TB [10].…”
Section: Introductionmentioning
confidence: 99%